LEGAL PROTECTION FOR TOURISTS IN AIR-TRAVEL TOUR PACKAGES IN INDONESIA: MAPPING AIRLINE RIGHTS–OBLIGATIONS AND THE NEED FOR JOINT LIABILITY STANDARDS - Diane Tangian; Bernadain Dainty Polii; Immanuel Christian Pontorondo; Bervie Fransel Rondonuwu (CV. TOTUS TUUS, 2026)
Air transportation is the backbone of tourist mobility in Indonesia, particularly within tour packages that bundle flights, accommodation, and destination activities. When disruptions occur—such as delays, cancellations, schedule changes, or overbooking—tourists often suffer “chain losses,” including forfeited hotel bookings and prepaid activities. Although Indonesia has sectoral legal instruments (aviation, tourism, and consumer protection), responsibility allocation in multi-party tour packages remains fragmented, creating uncertainty regarding who must compensate tourists beyond the airline ticket. This study aims to analyze the scope and limits of airline rights and obligations in flight-based tour packages, and to evaluate the adequacy of legal protection for tourists within tripartite relations involving airlines, travel agents, and destination service providers. Using a normative juridical method—combining statute and conceptual approaches with legal principle analysis—this research maps relevant norms and tests their coherence against principles of fairness, legal certainty, and consumer protection. The findings indicate that normative protection formally exists, yet implementation is ineffective because integrated contract standards are absent and joint liability among tourism businesses is not explicitly regulated. The study concludes that regulatory harmonization is required, alongside standardized tour-package contracts that clearly stipulate rights, obligations, risk allocation, compensation mechanisms for chain losses, and accessible dispute resolution. Future research should incorporate empirical case analysis of dispute outcomes, comparative models of joint liability in other jurisdictions, and regulatory impact assessments to test feasibility and enforcement pathways.